Diversity of γ- glutamyl peptides and oligosaccharides, the "kokumi" taste enhancers, in seeds from soybean mini core collections. Issue 3 (4th March 2018) - Shibata, Masayuki; Hirotsuka, Motohiko; Mizutani, Yukiko; Takahashi, Haruya; Kawada, Teruo; Matsumiya, Kentaro; Hayashi, Yukako; Matsumura, Yasuki
Abstract: Soybeans ( Glycine max (L, ) Merr, ) contain γ-glutamyl peptides and oligosaccharides, and these components play an important role in imparting the "kokumi" taste to foods. To gain insight into the genetic diversities and molecular mechanisms of accumulation of γ-glutamyl peptides and oligosaccharides in soybean, we measured the contents of these components using the Japan and World mini core collections. Similar to other previously reported traits, wide variations were detected among the accessions in the core collections with respect to the content of γ-glutamyl peptides and oligosaccharides. We found a positive relationship between the content of γ-glutamyl tyrosine and γ-glutamyl phenylalanine and between the content of raffinose and stachyose. Furthermore, there were unique accessions that included high levels of γ-glutamyl peptides and oligosaccharides. These accessions may be helpful in understanding the accumulation mechanism of γ-glutamyl peptides and oligosaccharides and to increase the "kokumi" taste components in soybean by performing a genetic analysis. Abstract : : Wide variations were detected among the JMC and WMC accessions for the content of the γ-glutamyl peptides and oligosaccharides.